2018
DOI: 10.1021/acs.jpcc.8b00814
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Proton Conductivity Arising from Hydrogen-Bond Patterns in Anhydrous Organic Single Crystals, Imidazolium Carboxylates

Abstract: Organic acid–base salts have attracted increasing attention as a promising candidate of anhydrous proton conductors. In this study, we have successfully disclosed the relationship between proton conductivity and hydrogen-bond (H-bond) interactions in such kinds of organic salts, composed of dicarboxylic acid and imidazole. We have grown high-quality single crystals of imidazolium succinate (Im-Suc) or glutarate (Im-Glu) with two-dimensional H-bonding networks and measured the proton conductivity within and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 90 publications
5
34
0
Order By: Relevance
“…In the present case, T o was ignored for simplicity. The natural logarithm of s is expressed as a function of temperature as follows: 51 Im-Suc (parallel to HB) 4.94 Â 10 À7 320 Im-Suc (perpendicular to HB) 3.55 Â 10 À9 378 Im-Glu (parallel to HB) 2.40 Â 10 À6 87 Im-Glu (perpendicular to HB) 5.92 Â 10 À8 157 Histamine 33 9.40 Â 10 À6 H1 (this work) 2.70 Â 10 À4 18.9 (at 330 K)…”
Section: Proton Conductivity Of H1mentioning
confidence: 99%
“…In the present case, T o was ignored for simplicity. The natural logarithm of s is expressed as a function of temperature as follows: 51 Im-Suc (parallel to HB) 4.94 Â 10 À7 320 Im-Suc (perpendicular to HB) 3.55 Â 10 À9 378 Im-Glu (parallel to HB) 2.40 Â 10 À6 87 Im-Glu (perpendicular to HB) 5.92 Â 10 À8 157 Histamine 33 9.40 Â 10 À6 H1 (this work) 2.70 Â 10 À4 18.9 (at 330 K)…”
Section: Proton Conductivity Of H1mentioning
confidence: 99%
“…Recent studies reveal the numerous requirements for a proton conductor to be used as an electrolyte in a fuel cell [ 5 , 6 ]. For instance, the conduction should be selective to protons, and the electrolyte must be an electrical insulator to prevent the internal short circuit of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Its strength is intermediate between the strengths of van der Waals interaction and covalent/coordination bonds; therefore, it has been widely utilized to indirectly control functionalities through structural regulation. 8,[10][11][12][13][14][15][16][17][18] Recent studies have demonstrated that the electrostatic and dynamic properties of protons in H-bonds can directly modulate the electronic functionalities of molecular crystals in the solid state. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] A clear strategy for controlling functionalities based on such electron-proton coupling is crucial to significantly expand a range of material designs for desired functionalities to pioneer novel physical properties and functionalities.…”
Section: Introductionmentioning
confidence: 99%